Antarctica looking forward - Jeffrey McGee; Elizabeth Leane (2019)
The ‘age of humans’ is significantly changing Antarctica and the Southern Ocean. Through different issues and disciplinary lenses, the contributions to this volume have explored the causes, effects and meanings of human interaction with the region. In this concluding chapter, we draw out some insights from these contributions as a group, suggesting four interrelated themes that capture the various ways in which the relationship between humans and the Antarctic continent is currently being perceived.